Planets In Your Hand (2017-2019) - Palafouta, Sofia; Gazeas, Kosmas; Christopoulou, Elena; Karampotsiou, Efsevia; Athanasopoulos, Dimitrios; Konstantinou, Anna; Tzouganatos, Lefteris; Kefala, Kyriaki; Papadami, Argiro; Trivyza, Marilia; Skliris, Vasilis; Chliaras, Vangelis (2019)
The Planets In Your Hand project was granted by Europlanet in the frame of Public Engagement Funding Scheme in 2017. It consists of a portable interactive exhibition of planetary surface models, embedded in square frames. The project offers the visitors a chance to see, learn and understand the diversity of the planetary surfaces in our Solar System, including the different conditions such as temperature, wind and atmosphere. Since the beginning of the project, the planetary surfaces have been presented to a wide range of audience, including visually impaired people, preliminary school and high school students as well as university researchers.